Oxygen evolution electrocatalyst as well as preparation method and application thereof

By growing Mn0.10Co0.90/CoCo2O4 composite on foam nickel hydrothermal method, the problem of difficulty in anode oxygen evolution reaction is solved, efficient and stable electrocatalytic oxygen evolution performance is achieved, cost is reduced, and industrial application potential is achieved.

CN119162609AInactive Publication Date: 2024-12-20GUANGXI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411361018.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-27
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing electrocatalytic water decomposition, the anode oxygen evolution reaction (OER) process is difficult. Ir and Ru-based oxide catalysts are expensive and unstable, which limit their large-scale industrial applications, seeking low prices, high crust reserves and good stability. non-precious metal-based OER catalyst.

Method used

Mn0.10Co0.90/CoCo2O4 composite material was grown in situ on the nickel foam of the carrier by hydrothermal method, and combined with heat treatment and sodium borohydride reduction method, an oxygen evolution electrocatalyst with excellent electrocatalytic oxygen evolution performance and full water decomposition performance was prepared. .

Benefits of technology

It achieves excellent OER performance and fast electron transfer rate under alkaline conditions, has good long-term stability and efficient catalytic performance, reduces catalyst shedding and production costs, and has industrial application potential.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119162609A_ABST
    Figure CN119162609A_ABST
Patent Text Reader

Abstract

The invention discloses an oxygen evolution electrocatalyst and a preparation method and application thereof, and belongs to the technical field of electrocatalytic oxygen evolution reaction.The oxygen evolution electrocatalyst is prepared by performing in-situ growth on a carrier foamed nickel through a hydrothermal reaction to obtain a MnO (OH) / CoCo2O4 composite material, then performing heat treatment on the MnO (OH) / CoCo2O4 composite material in a nitrogen atmosphere to obtain a Mn (OH) 2 / CoCo2O4 composite material, and finally reducing the Mn (OH) 2 / CoCo2O4 composite material by using NaBH4 to obtain the oxygen evolution electrocatalyst. The oxygen evolution electrocatalyst (Mn0. 10Co0. 90 / CoCo2O4) rich in oxygen vacancies has excellent electrocatalytic oxygen evolution performance and full water decomposition performance under alkaline conditions, also has extremely fast charge transfer rate and excellent stability, can be compared favorably with a noble metal-based catalyst, can be used as an excellent catalyst for electrocatalytic oxygen evolution reaction, and has good industrial application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalytic oxygen evolution reaction, and in particular relates to an oxygen evolution electrocatalyst and a preparation method and application thereof. Background Art

[0002] The development of society is accompanied by a large amount of energy consumption, and the traditional combustion of fossil fuels has brought not only energy depletion problems, but also environmental pollution problems, which will also pose a threat to the sustainable development of human society. Hydrogen energy is favored by people because of its high energy density and green sustainability. At present, the main methods of industrial hydrogen production mainly rely on steam methane reforming and coal gasification. These methods not only have high energy consumption and low gas purity, but also produce air pollutants. Electrocatalytic water decomposition to produce hydrogen has attracted widespread attention due to its high Faraday efficiency, environmental friendliness and green sustainability. It is also the most promising green commercial hydrogen production method.

[0003] Electrocatalytic water splitting includes the cathode hydrogen evolution reaction (HER reaction) involving 2 electron transfer and the anode oxygen evolution reaction (OER reaction) involving 4 electron transfer. The theoretical equilibrium potential of the HER reaction process is 0V, while the theoretical equilibrium potential of the OER reaction process is 1.23V. Therefore, the OER reaction process is more difficult than the HER reaction process, which also seriously affects the overall efficiency of water splitting. In the OER catalytic reaction process, Ir and Ru-based oxides have excellent catalytic performance. However, the large-scale industrial application of Ir and Ru-based oxides is limited by their high price, scarce reserves and weak stability. Therefore, the research and development of non-precious metal-based OER catalysts with low price, high crustal reserves and good stability is the current research focus in the field of electrocatalytic water splitting. Summary of the invention

[0004] In order to solve the above technical problems, the present invention proposes an oxygen evolution electrocatalyst and a preparation method and application thereof. The oxygen evolution electrocatalyst of the present invention is Mn 0.10 Co 0.90 / CoCo2O4 composite material has excellent electrocatalytic oxygen evolution performance and total water decomposition performance under alkaline conditions, and also has extremely fast charge transfer rate and excellent stability, which is comparable to precious metal-based catalysts. It can be used as an excellent catalyst for electrocatalytic oxygen evolution reaction and has good industrial application potential.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A method for preparing an oxygen evolution electrocatalyst comprises the following steps: in situ growing a MnO(OH) / CoCo2O4 composite material on a carrier by a hydrothermal method, then heat treating the MnO(OH) / CoCo2O4 composite material to obtain a Mn(OH)2 / CoCo2O4 composite material, and finally reducing the Mn(OH)2 / CoCo2O4 composite material with sodium borohydride (NaBH4) to obtain a Mn 0.10 Co 0.90 / CoCo2O4 composite material is the oxygen evolution electrocatalyst.

[0008] Preferably, the hydrothermal method is: adding urea (CO(NH2)2), ammonium fluoride (NH4F), manganese acetate tetrahydrate (Mn(Ac)2·4H2O) and cobalt acetate hexahydrate (Co(Ac)2·6H2O) into water together, stirring and ultrasonicating to obtain a reaction solution; then adding a carrier to the reaction solution, performing a hydrothermal reaction, and obtaining the MnO(OH) / CoCo2O4 composite material.

[0009] Preferably, the carrier is nickel foam. As a transition metal-based material, nickel foam has good electrical conductivity, which allows electrons to be quickly transmitted during the oxygen evolution reaction, thereby improving the efficiency of the electrocatalytic reaction. High electrical conductivity ensures that the catalyst surface can quickly accumulate and transfer the charge required for the reaction, thereby promoting the reaction. The three-dimensional network structure of nickel foam gives it a large specific surface area, and this large surface area allows the catalyst to more fully expose active sites, thereby increasing the contact opportunity between the catalyst and the reactant. In the oxygen evolution reaction, more active sites mean that more reactions can be carried out simultaneously, thereby improving the overall reaction rate and efficiency. The pore structure of nickel foam allows the catalyst loaded on its surface to be evenly distributed, and this even distribution not only contributes to the stability and durability of the catalyst, but also helps to improve the utilization rate of the catalyst. At the same time, good dispersibility also contributes to the rapid diffusion of reactants and products, reduces mass transfer resistance, and further improves reaction efficiency.

[0010] Preferably, the molar ratio of cobalt in cobalt acetate hexahydrate to manganese in manganese acetate tetrahydrate is 2:1.

[0011] For comparison, the total metal content was controlled to be 3 mmol, and experiments were conducted with the molar ratios of cobalt in cobalt acetate hexahydrate and manganese in manganese acetate tetrahydrate being (2.5:0.5, 1.5:1.5, 0.5:2.5, 3:0 and 0:3). From the obtained linear scanning curve of electrocatalytic oxygen evolution, it can be seen that when the molar ratio of cobalt in cobalt acetate hexahydrate and manganese in manganese acetate tetrahydrate is 2:1, the electrocatalytic performance is optimal.

[0012] More preferably, the molar ratio of urea, ammonium fluoride, cobalt acetate hexahydrate and manganese acetate tetrahydrate is 4.5:4:2:1.

[0013] Preferably, the temperature of the hydrothermal reaction is 120-180° C. and the time is 7 hours.

[0014] In contrast, the molar ratio of cobalt in cobalt acetate hexahydrate and manganese in manganese acetate tetrahydrate was controlled to be 2:1, and the hydrothermal reaction temperature was changed. It can be seen that when the temperature of the hydrothermal reaction is 140°C, the morphology is that the surface of the nanowire array is covered with an ultra-thin undulating nanosheet. This structure forms a cross-2D / 2D heterostructure with interconnected three-dimensional porous channels, thereby enhancing the penetration of electrolytes and the diffusion of oxygen, improving the catalytic performance, and the electrocatalytic performance is optimal.

[0015] More preferably, the temperature of the hydrothermal reaction is 140° C. and the time is 7 hours.

[0016] Preferably, the heat treatment is: in a nitrogen atmosphere, the MnO(OH) / CoCo2O4 composite material is heated at 5°C·min -1 The sample was heated to 400 °C at a heating rate of 100 °C, kept at this temperature for 2 h, and then cooled to room temperature.

[0017] Preferably, the reduction of the Mn(OH)2 / CoCo2O4 composite material by sodium borohydride comprises: adding the Mn(OH)2 / CoCo2O4 composite material to a sodium borohydride solution for reduction, and after the reduction is completed at room temperature, washing with water, and drying to obtain the Mn 0.10 Co 0.90 / CoCo2O4 composite materials.

[0018] The second technical solution of the present invention:

[0019] The present invention also provides an oxygen evolution electrocatalyst prepared according to the method.

[0020] The third technical solution of the present invention:

[0021] The present invention also provides the use of the oxygen evolution electrocatalyst in total water decomposition.

[0022] Compared with the prior art, the present invention has the following advantages and technical effects:

[0023] (1) The present invention in situ grows Mn on the carrier nickel foam by hydrothermal method, heat treatment method and sodium borohydride reduction method. 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst, which has oxygen vacancies, can promote electron transport and improve catalyst activity. 0.10 Co 0.90The / CoCo2O4 oxygen evolution electrocatalyst has excellent OER performance, fast electron transfer rate and good long-term stability under alkaline conditions. It also shows excellent water splitting performance and good stability in water splitting, which shows that the Mn prepared by the present invention 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst can be used as an excellent catalyst for electrocatalytic oxygen evolution reaction and has certain practical application potential.

[0024] (2) The preparation method of the present invention is simple, and the in-situ growth on the nickel foam reduces the shedding of the catalyst during use, greatly improves the catalytic efficiency and cost, and is convenient for commercial promotion; in addition, the Mn prepared by the present invention 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst can be directly used as the anode of the electrocatalytic oxygen evolution reaction without the need to re-prepare the electrode, and is very convenient to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0026] Figure 1 This is the X-ray powder diffraction pattern of the MnO(OH) / CoCo2O4 composite material prepared in Example 1.

[0027] Figure 2 This is the X-ray powder diffraction pattern of the Mn(OH)2 / CoCo2O4 composite material prepared in Example 1.

[0028] Figure 3 Mn prepared in Example 1 0.10 Co 0.90 X-ray powder diffraction pattern of / CoCo2O4 oxygen evolution electrocatalyst.

[0029] Figure 4 The scanning electron microscope image of the composite material prepared in Example 1, wherein a is MnO(OH) / CoCo2O4; b is Mn(OH)2 / CoCo2O4; c is Mn 0.10 Co 0.90 / CoCo2O4.

[0030] Figure 5 Mn prepared in Example 1 0.10 Co 0.90 / Various electron microscope images of CoCo2O4 oxygen evolution electrocatalysts, where a is Mn 0.10 Co 0.90 / TEM image of CoCo2O4, b is Mn0.10 Co 0.90 / CoCo2O4 high resolution transmission electron microscopy image, c is Mn 0.10 Co 0.90 / CoCo2O4 high-angle annular dark-field transmission electron microscopy image, d is Mn 0.10 Co 0.90 / Distribution map of CoCo2O4 elements.

[0031] Figure 6 Mn prepared in Example 1 0.10 Co 0.90 N2 adsorption / desorption isotherms and pore size distribution of CoCo2O4 / CoO4 oxygen evolution electrocatalyst.

[0032] Figure 7 The MnO(OH) / CoCo2O4 composite material, Mn(OH)2 / CoCo2O4 composite material and Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst and the electron paramagnetic resonance spectrum of the Mn3O4 / Co(OH)2 electrocatalyst prepared in Comparative Example 3.

[0033] Figure 8 These are scanning electron microscope images of the electrocatalysts prepared in Comparative Example 1, Comparative Example 2, Comparative Example 6, Comparative Example 7 and Comparative Example 8, wherein a is a scanning electron microscope image of the Mn2O3 / Mn(OH)2 electrocatalyst prepared in Comparative Example 2, b is a scanning electron microscope image of the Co(OH)2 / CoCo2O4 electrocatalyst prepared in Comparative Example 1, c is a scanning electron microscope image of the electrocatalyst prepared in Comparative Example 6, d is a scanning electron microscope image of the electrocatalyst prepared in Comparative Example 7, and e is a scanning electron microscope image of the electrocatalyst prepared in Comparative Example 8.

[0034] Fig. 9 These are scanning electron microscope images of the electrocatalysts prepared in Comparative Example 9, Comparative Example 10, Comparative Example 11 and Comparative Example 12, wherein a is Comparative Example 9, b is Comparative Example 10, c is Comparative Example 11, and d is Comparative Example 12.

[0035] Fig.10 Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst, the Co(OH)2 / CoCo2O4 electrocatalyst prepared in Comparative Example 1, and the Mn2O3 / Mn(OH)2 electrocatalyst prepared in Comparative Example 2, wherein a is the 2p spectrum of Co, b is the 2p spectrum of Mn, and c is the 1s spectrum of O.

[0036] Fig.11The MnO(OH) / CoCo2O4 composite material, Mn(OH)2 / CoCo2O4 composite material and Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst, the electrocatalyst prepared in Comparative Examples 1-2 and the RuO2 electrode material prepared in Comparative Example 5 were tested for electrochemical properties in 1.0M KOH, wherein a is a linear scan curve for electrocatalytic oxygen evolution; b is a Tafel slope diagram; c is a diagram for comparing various performance results; d is a double-layer capacitance diagram; e is a Tafel slope diagram of the catalyst reported in the prior art (wherein This work is a MnO(OH) / CoCo2O4 composite material prepared in Example 1); f is an electrochemical impedance spectroscopy diagram; g is a diagram for comparing the Mn 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst three-electrode stability test results and contact angle test results.

[0037] Fig.12 The electrochemical performance test graphs of different molar ratios of cobalt in cobalt acetate hexahydrate and manganese in manganese acetate tetrahydrate prepared in Example 1 and Comparative Examples 1, 2, 6, 7 and 8, wherein a is a linear scanning curve for electrocatalytic oxygen evolution; b is a Tafel slope graph; c is an electrochemical impedance spectrum graph; and d is a double-layer capacitance graph.

[0038] Fig.13 Electrochemical performance test graphs of different hydrothermal reaction times were prepared for Example 1 and Comparative Examples 9, 10, 11 and 12. Among them, a is the linear scanning curve of electrocatalytic oxygen evolution; b is the Tafel slope graph; c is the electrochemical impedance spectroscopy graph; d is the double layer capacitance graph.

[0039] Fig.14 Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst full water decomposition process and results, where a is a schematic diagram of full water decomposition; b is a two-electrode test; c is a comparison of the performance results of the two electrodes; d is a Mn 0.10 Co 0.90 Comparison results of the cell voltage of the full water decomposition of the two-electrode system composed of / CoCo2O4 and Pt / C electrode materials and the OER catalyst reported in the prior art (where This work is the MnO(OH) / CoCo2O4 composite material prepared in Example 1); e is Mn 0.10 Co 0.90 Stability test results of the two-electrode system composed of / CoCo2O4 and Pt / C electrode materials. DETAILED DESCRIPTION

[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0045] Unless otherwise specified, the room temperature in the present invention is 25±2°C.

[0046] All raw materials used in the embodiments of the present invention are commercially available.

[0047] The technical solution of the present invention is further illustrated by the following embodiments.

[0048] Example 1

[0049] A Mn 0.10 Co 0.90 / Preparation method of CoCo2O4 oxygen evolution electrocatalyst:

[0050] (1) Pretreatment of nickel foam: Cut commercial nickel foam into 1.5×3 cm 2The pieces were then ultrasonically washed in 0.5 mol / L sulfuric acid solution, deionized water and ethanol for 15 min each, rinsed with deionized water and dried naturally for later use.

[0051] (2) Preparation of reaction solution: 4.5 mmol urea, 4.0 mmol ammonium fluoride, 2.0 mmol cobalt acetate hexahydrate and 1.0 mmol manganese acetate tetrahydrate were weighed and added into 40 mL deionized water solution and stirred for 30 minutes to obtain a uniform solution (i.e., in this embodiment, Co:Mn=2:1, molar ratio, the same below).

[0052] (3) Hydrothermal reaction: The clean nickel foam treated in step (1) is placed in the uniform solution prepared in step (2), placed in a reactor, and then kept in an oven at 140° C. for 7 hours. After the reaction is completed, it is naturally cooled to room temperature, and then the synthesized product is rinsed with deionized water and then placed in an oven at 60° C. for 6 hours to obtain a MnO(OH) / CoCo2O4 composite material.

[0053] (4) Heat treatment reaction: The MnO(OH) / CoCo2O4 composite material obtained in step (3) was placed in the middle of a quartz tube and heated at 5°C min-1 under a N2 atmosphere. -1 The temperature was raised to 400°C at a rate of 1.25 °C, kept at that temperature for 2 hours, and naturally cooled to room temperature to obtain a Mn(OH)2 / CoCo2O4 composite material.

[0054] (5) Sodium borohydride reduction reaction: Weigh 0.1 g of sodium borohydride and dissolve it in 20 mL of deionized water and disperse it evenly by ultrasonication to obtain a sodium borohydride solution. Then, the Mn(OH)2 / CoCo2O4 composite material obtained in step (4) was placed in the above sodium borohydride solution and reacted at room temperature for 5 hours. After taking it out, it was rinsed with a large amount of deionized water until the surface of the material was neutral, and then transferred to an oven at 60°C and dried for 6 hours to obtain Mn 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst.

[0055] Comparative Example 1

[0056] A method for preparing a Co(OH)2 / CoCo2O4 electrocatalyst:

[0057] The same as Example 1, except that in step (2), only cobalt acetate hexahydrate is added, and manganese acetate tetrahydrate is not added.

[0058] Comparative Example 2

[0059] A method for preparing a Mn2O3 / Mn(OH)2 electrocatalyst:

[0060] The same as Example 1, except that in step (2), only manganese acetate tetrahydrate is added, and cobalt acetate hexahydrate is not added.

[0061] Comparative Example 3

[0062] A method for preparing a Mn3O4 / Co(OH)2 electrocatalyst:

[0063] (1) Pretreatment of nickel foam: Cut commercial nickel foam into 1.5×3 cm 2 The pieces were then ultrasonically washed in 0.5 mol / L sulfuric acid solution, deionized water and ethanol for 15 min each, rinsed with deionized water and dried naturally for later use.

[0064] (2) Preparation of reaction solution: 4.5 mmol urea, 4.0 mmol ammonium fluoride, 2.0 mmol cobalt acetate hexahydrate, and 1.0 mmol manganese acetate tetrahydrate were weighed and added into 40 mL deionized water solution, and stirred for 30 minutes to obtain a uniform solution.

[0065] (3) Hydrothermal reaction: The clean nickel foam treated in step (1) is placed in the uniform solution prepared in step (2), placed in a reactor, and then kept in an oven at 140° C. for 7 hours. After the reaction is completed, it is naturally cooled to room temperature, and then the synthesized product is rinsed with deionized water and then placed in an oven at 60° C. for 6 hours to obtain a MnO(OH) / CoCo2O4 composite material.

[0066] (4) Sodium borohydride reduction reaction: Weigh 0.1 g of sodium borohydride and dissolve it in 20 mL of deionized water. After ultrasonic dispersion, the MnO(OH) / CoCo2O4 composite material obtained in step (3) was placed in the sodium borohydride solution and reacted at room temperature for 5 hours. After taking it out, rinse it with a large amount of deionized water, transfer it to a 60°C oven and dry it for 6 hours to obtain a Mn3O4 / Co(OH)2 electrocatalyst.

[0067] Comparative Example 4

[0068] Preparation of Pt / C electrode materials:

[0069] 2 mg Pt / C (commercially available) was weighed and added to a mixed solution of 200 μL deionized water, 200 μL anhydrous ethanol, and 10 μL Nafion solution. The mixture was dissolved by ultrasonication for 30 minutes. Then, the Pt / C slurry homogenized by ultrasonication was dropped on a 1 cm 2 on nickel foam and dried at room temperature for later use.

[0070] Comparative Example 5

[0071] Preparation of RuO2 electrode materials:

[0072] 2 mg of RuO2 (commercially available) was weighed and added to a mixed solution of 200 μL of deionized water, 200 μL of anhydrous ethanol, and 10 μL of Nafion solution. The mixture was dissolved by ultrasonication for 30 minutes. Then, the RuO2 slurry homogenized by ultrasonication was dropped on a 1 cm 2 on nickel foam and dried at room temperature for later use.

[0073] Comparative Example 6

[0074] The same as Example 1, the total metal content is controlled to be 3 mmol, the only difference is that in step (2), the amount of cobalt acetate hexahydrate added is 2.5 mmol, and the amount of manganese acetate tetrahydrate added is 0.5 mmol, that is, in this comparative example, Co:Mn=2.5:0.5.

[0075] Comparative Example 7

[0076] The same as Example 1, the total metal content is controlled to be 3 mmol, the only difference is that in step (2), the amount of cobalt acetate hexahydrate added is 1.5 mmol, and the amount of manganese acetate tetrahydrate added is 1.5 mmol, that is, in this comparative example, Co:Mn=1.5:1.5.

[0077] Comparative Example 8

[0078] The same as Example 1, the total metal content is controlled to be 3 mmol, the only difference is that in step (2), the amount of cobalt acetate hexahydrate added is 0.5 mmol, and the amount of manganese acetate tetrahydrate added is 2.5 mmol, that is, in this comparative example, Co:Mn=0.5:2.5.

[0079] Comparative Example 9

[0080] Same as Example 1, except that the hydrothermal reaction temperature in step (3) is 100°C.

[0081] Comparative Example 10

[0082] Same as Example 1, except that the hydrothermal reaction temperature in step (3) is 120°C.

[0083] Comparative Example 11

[0084] Same as Example 1, except that the hydrothermal reaction temperature in step (3) is 160°C.

[0085] Comparative Example 12

[0086] Same as Example 1, except that the hydrothermal reaction temperature in step (3) is 180°C.

[0087] By comparing the morphology, Figure 8 and Fig. 9It can be found that when the temperature of the hydrothermal reaction is 140°C and the molar ratio of cobalt in cobalt acetate hexahydrate and manganese in manganese acetate tetrahydrate is 2:1, the morphology is that the surface of the nanowire array is covered with an ultra-thin undulating nanosheet. This structure forms a cross-2D / 2D heterostructure with interconnected three-dimensional porous channels, which enhances the penetration of electrolytes and the diffusion of oxygen, improves the catalytic performance, and the electrocatalytic performance is optimal. By comparison Fig.13 , Fig.14 The electrocatalytic performance test showed that when the temperature of the hydrothermal reaction was 140°C and the molar ratio of cobalt in cobalt acetate hexahydrate to manganese in manganese acetate tetrahydrate was 2:1, the electrocatalytic performance was the best, the Tafel slope was the lowest, the electrochemical impedance was the smallest, and the double-layer capacitance value was the largest.

[0088] Test method: The electrocatalytic oxygen evolution test was carried out on an electrochemical workstation (Bio-Logic VMP3, France) using a three-electrode system. 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst is used as working electrode, graphite plate is used as counter electrode, saturated calomel electrode is used as reference electrode, 1.0M KOH solution is used as electrolyte, test temperature is 25°C, scanning speed is 5mV / s. The electrode potential is obtained by saturated calomel electrode, and reversible hydrogen electrode (RHE) and impedance compensation correction are performed. All potentials of the present invention are obtained according to the following Nernst equation:

[0089] E RHE =E SCE +0.241+0.059pH-iR

[0090] Where i is the tested current (A), and R is the solution impedance (Ω); the water electrolysis test was carried out on an electrochemical workstation (Bio-Logic VMP3, France) using a two-electrode system.

[0091] Water splitting test: A two-electrode system was used on an electrochemical workstation (Bio-Logic VMP3, France), consisting of an anode and a cathode. 1.0 mol / L potassium hydroxide solution was used as the electrolyte, the test temperature was 25°C, the scan rate was 2mV / s, and the scan range was 0-2.5V. The oxygen evolution reaction was the anode reaction, and the oxygen evolution reaction electrode was the Mn prepared in Example 1. 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst or the RuO2 electrode material prepared in Comparative Example 5; the hydrogen evolution reaction is the cathode reaction, and the hydrogen evolution reaction electrode is the Pt / C electrode material prepared in Comparative Example 4.

[0092] Test Results

[0093] Effect verification

[0094] 1. Characterization of structure, composition and morphology

[0095] (1) Figure 1 The X-ray powder diffraction pattern of the MnO(OH) / CoCo2O4 composite material prepared in Example 1 of the present invention is shown in FIG. Figure 1 It can be seen that the MnO(OH) / CoCo2O4 composite material prepared in Example 1 has characteristic peaks of X-ray powder diffraction typical of MnO(OH) and CoCo2O4. Figure 2 The X-ray powder diffraction pattern of the Mn(OH)2 / CoCo2O4 composite material prepared in Example 1 of the present invention is shown in FIG. Figure 2 It can be seen that the Mn(OH)2 / CoCo2O4 composite material prepared in Example 1 has characteristic peaks of X-ray powder diffraction typical of Mn(OH)2 and CoCo2O4. Figure 3 Mn prepared in Example 1 of the present invention 0.10 Co 0.90 X-ray powder diffraction pattern of / CoCo2O4 oxygen evolution electrocatalyst, by Figure 3 It can be seen that the Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst with Mn 0.10 Co 0.90 And the characteristic peaks of typical X-ray powder diffraction of CoCo2O4.

[0096] (2) Figure 4 The MnO(OH) / CoCo2O4 composite material, Mn(OH)2 / CoCo2O4 composite material and Mn prepared in Example 1 0.10 Co 0.90 Scanning electron micrograph of / CoCo2O4 oxygen evolution electrocatalyst. Figure 4 Figure a is a scanning electron microscope image of the MnO(OH) / CoCo2O4 composite material prepared in Example 1. It can be seen that MnO(OH) / CoCo2O4 is a nanoflower morphology composed of needle tips. Figure 4 Figure b is a scanning electron microscope image of the Mn(OH)2 / CoCo2O4 composite material prepared in Example 1. It can be seen that after high-temperature calcination at 400°C, the nanoflower morphology of Mn(OH)2 / CoCo2O4 changes from the original needle-tip nanoflower morphology to a more elongated needle-tip nanoflower morphology, which indicates that high-temperature calcination has an impact on its morphology. Figure 4 Where c is Mn 0.10 Co 0.90 Scanning electron micrograph of CoCo2O4 oxygen evolution electrocatalyst shows that Mn0.10 Co 0.90 / CoCo2O4 is a morphology of cross-linked nanosheets growing on slender needle-tip nanoflowers, which shows that the reduction of sodium borohydride also affects its original morphology and plays an important role in the change of its electrochemical properties.

[0097] (3) Figure 5 Mn prepared in Example 1 0.10 Co 0.90 Various electron microscope images of CoCo2O4 oxygen evolution electrocatalysts; a is Mn 0.10 Co 0.90 / TEM image of CoCo2O4 oxygen evolution electrocatalyst, Figure 5 The a further confirmed that Mn 0.10 Co 0.90 / CoCo2O4 is a needle-like nanoflower morphology. b is Mn 0.10 Co 0.90 High-resolution transmission electron microscopy image of CoCo2O4 oxygen evolution electrocatalyst Figure 5 As can be seen in b, Mn 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst lattice fringe spacing is 0.128nm and 0.257nm, corresponding to CoCo2O4 and Mn 0.10 Co 0.90 The interplanar spacings of CoCo2O4 and Mn are (620) and (011), respectively. The inset is a lattice analysis diagram, corresponding to 0.10 Co 0.90 lattice spacing. Figure 5 The selected area electron diffraction (SAED) pattern in the middle c shows the (620), (511) planes of CoCo2O4 and Mn 0.10 Co 0.90 The (011) plane has clear diffraction rings. Figure 5 Where d is Mn 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst distribution diagram, it can be seen that Mn 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst has uniform distribution of various elements.

[0098] (4) Figure 6 Mn prepared in Example 1 0.10 Co 0.90 N2 adsorption / desorption isotherms and pore size distribution of CoCo2O4 / CoO2 electrocatalyst. Figure 6 Mn can be analyzed 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst shows a typical type III isotherm with mesoporous characteristics and obvious hysteresis loop. 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst BET surface area (76.20 m 2 ·g -1 ), which helps to expose more active sites, promote electrolyte diffusion, and improve gas emission.

[0099] (5) Figure 7 The MnO(OH) / CoCo2O4 composite material, Mn(OH)2 / CoCo2O4 composite material and Mn prepared in Example 1 0.10 Co 0.90 Electron paramagnetic resonance spectra of the Mn3O4 / Co(OH)2 electrocatalyst prepared in Example 3. Figure 7 It can be seen that the Mn prepared in Example 1 of the present invention 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst showed a signal related to the unpaired electrons of sulfur vacancies at g = 2.005, indicating that Mn 0.10 Co 0.90 There are oxygen vacancies in the MnO(OH) / CoCo2O4 oxygen evolution electrocatalyst, but no vacancies are produced in the MnO(OH)2 / CoCo2O4 composite material. Instead, metal vacancies are produced in the Mn(OH)2 / CoCo2O4 composite material. This shows that the sodium borohydride reduction method can generate oxygen vacancies in the catalyst, thereby modifying the electronic structure of the catalyst and further improving the conductivity of the catalyst.

[0100] (6) Figure 8 The following are scanning electron microscope images of the electrocatalysts prepared in Comparative Example 1, Comparative Example 2, Comparative Example 6, Comparative Example 7 and Comparative Example 8. a is a scanning electron microscope image of the Mn2O3 / Mn(OH)2 electrocatalyst prepared in Comparative Example 2. It can be seen that its morphology is nano-blocks and stacked together. b is a scanning electron microscope image of the Co(OH)2 / CoCo2O4 electrocatalyst prepared in Comparative Example 1. It can be seen that its morphology is nano-cotton-like. ce are scanning electron microscope images of electrocatalysts with different cobalt and manganese metal contents prepared in Comparative Example 6, Comparative Example 7 and Comparative Example 8, respectively. It can be concluded that as the content of manganese ions increases, its morphology gradually stacks up, the larger the stacking structure, the fewer active sites exposed on its surface, and the worse the electrocatalytic performance. Figure 4 and Figure 8It can be judged that when the molar ratio of cobalt in cobalt acetate hexahydrate and manganese in manganese acetate tetrahydrate is 2:1, its morphology is that the surface of the nanowire array is covered with an ultra-thin undulating nanosheet. This structure forms a cross-2D / 2D heterostructure with interconnected three-dimensional porous channels, thereby enhancing the penetration of electrolytes and the diffusion of oxygen, improving the catalytic performance, and the electrocatalytic performance is optimal.

[0101] (7) Fig. 9 The scanning electron microscope images of the electrocatalysts prepared in Comparative Examples 9, 10, 11 and 12, where a is Comparative Example 9, b is Comparative Example 10, c is Comparative Example 11, and d is Comparative Example 12. It can be seen that with the increase of the hydrothermal reaction time, the morphology of the catalyst does not change much. However, comparing the electrocatalytic performance graphs at different temperatures, the electrocatalyst at 140°C has the best performance, so the optimal temperature is determined to be 140°C.

[0102] (8) Fig.10 Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst, the Co(OH)2 / CoCo2O4 electrocatalyst prepared in Comparative Example 1, and the Mn2O3 / Mn(OH)2 electrocatalyst prepared in Comparative Example 2. Figure 8 a is the 2p spectrum of Co, Figure 8 Where b is the 2p spectrum of Mn, Figure 8 In the figure, c is the 1s spectrum of O. Figure 8 As can be seen from a, compared with Co(OH)2 / CoCo2O4, Mn 0.10 Co 0.90 / CoCo2O4, Co 2p moves to a lower binding energy. Figure 8 As can be seen in Figure b, compared with Mn2O3 / Mn(OH)2, Mn 0.10 Co 0.90 In / CoCo2O4, the Mn 2p moves to a higher binding energy, which indicates that Mn doping modulates the electronic state of the Co center, resulting in a stronger electronic interaction between Co and Mn.

[0103] 2. The electrochemical test results are as follows:

[0104] (1) Fig.11 The MnO(OH) / CoCo2O4 composite material, Mn(OH)2 / CoCo2O4 composite material and Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst, the electrocatalyst prepared in Comparative Examples 1-2 and the RuO2 electrode material prepared in Comparative Example 5 were tested for electrochemical properties in 1.0M KOH, wherein a is a linear scan curve for electrocatalytic oxygen evolution; b is a Tafel slope diagram; c is a diagram for comparing various performances; d is a double layer capacitance diagram; e is a Tafel slope diagram of the catalyst reported in the prior art; f is an electrochemical impedance spectrum diagram; g is a diagram for Mn 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst three-electrode stability test results. Fig. 9 It can be seen from af that the Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst has excellent electrochemical oxygen evolution performance and fast charge transfer rate. Fig. 9 The three-electrode stability of g is known to be 50 mA cm -2 After continuous operation for 280 hours under the same conditions, the overpotential hardly increased, further demonstrating its excellent stability. Fig. 9 The contact angle test of the catalyst with medium g can obtain the Mn 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst exhibits superhydrophilicity, because when water droplets fall on the electrode surface, the water droplets immediately penetrate into the electrode surface, reducing the static contact angle to zero. This superhydrophilicity promotes close contact between the electrolyte and the electrode and rapid diffusion of the electrolyte, enhances the transfer of mass and charge, and accelerates the reaction kinetics. The water contact angles on the Co(OH)2 / CoCo2O4 catalyst and the Mn2O3 / Mn(OH)2 catalyst are 40.2° and 131.2°, respectively.

[0105] Fig.11 The catalysts reported in the prior art are detailed in Table 1.

[0106] Table 1

[0107]

[0108]

[0109] (2) Fig.12 The electrochemical performance test diagrams of different molar ratios of cobalt in cobalt acetate hexahydrate and manganese in manganese acetate tetrahydrate prepared in Example 1 and Comparative Examples 1, 2, 6, 7 and 8. Wherein, a is the linear scanning curve of electrocatalytic oxygen evolution; b is the Tafel slope diagram; c is the electrochemical impedance spectrum diagram; d is the double layer capacitance diagram. According to the comparison, it can be concluded that when the molar ratio of cobalt in cobalt acetate hexahydrate and manganese in manganese acetate tetrahydrate is 2:1, its electrochemical performance is the best, the Tafel slope is the lowest, the electrochemical impedance is the smallest, and the double layer capacitance value is the largest.

[0110] (3) Fig.13 Electrochemical performance test graphs of different hydrothermal reaction times were prepared for Example 1 and Comparative Examples 9, 10, 11 and 12. Among them, a is the linear scanning curve of electrocatalytic oxygen evolution; b is the Tafel slope graph; c is the electrochemical impedance spectrum; d is the double layer capacitance graph. According to the comparison, it can be concluded that when the hydrothermal reaction is 140°C, its electrochemical performance is the best, the Tafel slope is the lowest, the electrochemical impedance is the smallest, and the double layer capacitance value is the largest.

[0111] (4) Fig.14 Mn prepared in Example 1 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst full water decomposition process and results, where a is a schematic diagram of full water decomposition; b is a two-electrode test; c is a comparison of the performance results of the two electrodes; d is a Mn 0.10 Co 0.90 Comparison of the cell voltage of the water splitting cell composed of the two-electrode system composed of / CoCo2O4 and Pt / C electrode materials and the OER catalyst reported in the prior art; e is Mn 0.10 Co 0.90 Stability test results of the two-electrode system consisting of Co / Co2O4 and Pt / C electrode materials. Fig.10 It can be seen from ad that the Mn prepared by the present invention 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst has excellent overall water splitting performance, and is superior to the two electrodes composed of Pt / C and RuO2, and is also superior to most OER catalysts reported in the prior art. Fig.10 From d, we can know that Mn 0.10 Co 0.90 The two-electrode system consisting of CoCo2O4 and Pt / C electrode materials was -2 It can run stably for 135 hours under this condition, which also shows that the Mn prepared by the present invention 0.10 Co 0.90 / CoCo2O4 oxygen evolution electrocatalyst has good stability and durability.

[0112] Fig.14 The OER catalysts reported in the prior art are detailed in Table 2.

[0113] Table 2

[0114]

[0115]

[0116] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing an oxygen evolution electrocatalyst, characterized in that: The following steps are involved: The MnO(OH) / CoCo2O4 composite material is in situ grown on a carrier by a hydrothermal method, and then the MnO(OH) / CoCo2O4 composite material is heat treated to obtain a Mn(OH)2 / CoCo2O4 composite material, and finally the Mn(OH)2 / CoCo2O4 composite material is reduced by sodium borohydride to obtain a Mn 0.10 Co 0.90 / CoCo2O4 composite material is the oxygen evolution electrocatalyst.

2. The method for preparing an oxygen evolution electrocatalyst according to claim 1, characterized in that: The hydrothermal method comprises: adding urea, ammonium fluoride, manganese acetate tetrahydrate and cobalt acetate hexahydrate into water, stirring and ultrasonicating to obtain a reaction solution; then adding a carrier into the reaction solution, performing a hydrothermal reaction, and obtaining the MnO(OH) / CoCo2O4 composite material.

3. The method for preparing an oxygen evolution electrocatalyst according to claim 2, characterized in that: The molar ratio of cobalt in cobalt acetate hexahydrate to manganese in manganese acetate tetrahydrate is 2:

1.

4. The method for preparing an oxygen evolution electrocatalyst according to claim 2, characterized in that: The temperature of the hydrothermal reaction is 120-180° C. and the time is 7 hours.

5. The method for preparing an oxygen evolution electrocatalyst according to claim 4, characterized in that: The temperature of the hydrothermal reaction is 140° C. and the time is 7 hours.

6. The method for preparing an oxygen evolution electrocatalyst according to claim 1, characterized in that: The heat treatment comprises: heating the MnO(OH) / CoCo2O4 composite material at 5°C·min in a nitrogen atmosphere. -1 The sample was heated to 400 °C at a heating rate of 100 °C, kept at this temperature for 2 h, and then cooled to room temperature.

7. The method for preparing an oxygen evolution electrocatalyst according to claim 1, characterized in that: The method of reducing the Mn(OH)2 / CoCo2O4 composite material by sodium borohydride is as follows: adding the Mn(OH)2 / CoCo2O4 composite material to a sodium borohydride solution for reduction, and after the reduction is completed at room temperature, washing with water, and drying to obtain the Mn 0.10 Co 0.90 / CoCo2O4 composite materials.

8. An oxygen evolution electrocatalyst, characterized in that Prepared according to the preparation method according to any one of claims 1 to 7.

9. Use of the oxygen evolution electrocatalyst according to claim 8 in overall water splitting.